Potential Inhibition of Melaleuca leucadendron L. Compounds Against the NSP5 SARS CoV-2 Protein - Melani, Ira Resmi; Wafi, Muhammad Farid; Riandinata, Mohammad Reza; Halim, Putri Aulawiya Rosyida; Muti'ah, Roihatul; Santosaningsih, Dewi (Indonesian Journal of Cancer Chemoprevention, 2022)
COVID-19 is an infectious disease caused by Severe Acute Respiratory Syndrome (SARS-CoV-2), causing a global health emergency as a pandemic disease. The lack of certain drug molecules or treatment strategies to fight this disease makes it worse. Therefore, effective drug molecules are needed to fight COVID-19. Non Structural Protein (NSP5) or called Main Protease (Mpro) of SARS CoV 2, a key component of this viral replication, is considered a key target for anti-COVID-19 drug development. The purpose of this study is to determine whether the compounds in the Melaleuca leucadendron L. plant such as 1,8-cineole, terpene, guaiol, linalol, α-selinenol, β-eudesmol and γ-eudesmol are predicted to have antiviral activity for COVID-19. Interaction of compounds with NSP5 with PDB code 6WNP analyzed using molecular docking with Molegro Virtual Docker. Based on binding affinity, the highest potential as an anti-viral is Terpineol with binding energy (-119.743 kcal/mol). The results of the interaction showed that terpinol has similarities in all three amino acid residues namely Cys 145, Gly 143, and Glu 166 with remdesivir and native ligand. Melaleuca leucadendron L. may represent a potential herbal treatment to act as: COVID-19 NSP5, however these findings must be validated in vitro and in vivo.Keywords: COVID-19, In Silico, NSP5/ 6WNP, Melaleuca leucadendron L.